Sistem Informasi Geografis Pemetaan Kepemilikan Tanah (Studi Kasus di RT 05 RW 03 Desa Klaling) - Wahyu Cahyoaji; Muhammad Imam Ghozali; Wibowo Harry Sugiharto (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2024)
This research entitled " Geographic Information System for Mapping Land Ownership (Case Study in RT 05 RW 03 Klaling Village)" aims to develop a web-based application that facilitates public access to land information. In the era of information technology advancement, limited access to land information in Klaling Village is a SIGnificant problem, where people still have to visit the village office or land office manually, which is often inefficient. The research method used is the Waterfall method, which allows system development to be carried out in a structured and planned manner. The Geographic Information System (GIS) application developed in this study has succeeded in providing land ownership information online, allowing residents to search for and measure land easily. In addition, this system is expected to reduce the possibility of fraud in the shifting of land ownership rights. The results of the study show that the implementation of web-based GIS in Klaling Village increases the efficiency of access to land information. Residents can quickly and easily see the status of land ownership in their area, which reduces dependence on slow and inefficient traditional methods. The process of searching and verifying land data that previously took time can now be done online, increasing operational efficiency for all parties involved.  The conclusion of this study confirms that the information system developed not only increases the accessibility of land information, but also supports better land management. Thus, this application has the potential to provide a positive impact on the community and government in making decisions related to land.